L'adaptation en Île-de-France entre injonction et recyclage. Techniques et politiques de la société de l'incertitude - Magali Reghezza-Zitt; Samuel Rufat (Développement Durable et Territoires)
As we shift from a society of risk to a society of uncertainty, both adaptation and resilience appear to be pragmatic answers to theoretical and operational dead-ends. In just a few years, adaptation has become an injunction and is seen as the central piece of coping strategies against threats and uncertainty. This use of the concept of adaptation by practitioners is however often in name only : it is less a paradigm shift than a rebranding of old technical solutions. This rebranding often comes with a depolitization and a naturalization of public choice. We illustrate these issues with the case of the Île-de-France, by deconstructing public discourses, thereby showing the importance of repoliticizing adaptation.